2007
DOI: 10.1097/nrl.0b013e31814db093
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Hand Palsy Due to Cortical Infarction: Localization of the Motor Hand Area

Abstract: Our findings indicate that the hand area in the cerebral motor cortex is located in the middle to lower portion of the anterior wall of the central sulcus, that is, in Brodmann area 4. We present our 8 patients showing isolated hand palsy due to a discrete cortical infarction on MRI to expand the knowledge about cortical localization of the hand area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 14 publications
2
34
0
2
Order By: Relevance
“…It is known that pure motor hemiparesis resulting from acute stroke can occur in the PLIC, corona radiata, pontine base and/or ventromedial medulla, with the PLIC being the most frequent site of lesions (5). It has been reported that pure motor monoparesis is rarely caused by lacunar infarctions and that "isolated hand palsy" can be caused by cortical infarctions located in the hand motor area (2,6). To the best of our knowledge, there have been no previous reports of pure motor hemiparesis manifesting primarily as pseudoperipheral palsy caused by a PLIC lesion.…”
Section: Discussionmentioning
confidence: 95%
“…It is known that pure motor hemiparesis resulting from acute stroke can occur in the PLIC, corona radiata, pontine base and/or ventromedial medulla, with the PLIC being the most frequent site of lesions (5). It has been reported that pure motor monoparesis is rarely caused by lacunar infarctions and that "isolated hand palsy" can be caused by cortical infarctions located in the hand motor area (2,6). To the best of our knowledge, there have been no previous reports of pure motor hemiparesis manifesting primarily as pseudoperipheral palsy caused by a PLIC lesion.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, isolated hand pareses without distinction of the specific nerve side involvement were examined for identification of the motor hand area in the brain. Çelebisoy et al [14] reported that the hand area in the cerebral motor cortex is located in the middle to lower portion of the anterior wall of the central sulcus. Lesions of this region may result in isolated hand paresis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Celebisoy et al [7] noted that the hand area in the cerebral motor cortex was located in the middle to lower portion of the anterior wall of the central sulcus. However, in the cerebral motor cortex, detailed vascular supply remains uncertain.…”
Section: Discussionmentioning
confidence: 99%